Assessment of potential probiotic lactic acid bacteria in rice-based fermented products of Southern Assam, Northeast India - Yumnam, Hanna; Nath, Soumitra; Chakraborty, Pragya; Sharma, Indu (Frontiers in Microbiology, 2025)
IntroductionIndigenous ethnic fermented products have gained recognition as valuable sources of probiotic bacteria, which play a crucial role in maintaining the natural balance of the gut microbiota.MethodsTwenty-five samples of rice-based fermented products were analyzed, recovering 16 LAB isolates, preliminarily identified by morphological and biochemical tests, and further confirmed using 16S rRNA gene sequencing. Subsequent in vitro assessments, safety evaluations and technological properties were performed on all isolated strains.ResultsThe potential probiotic strains were able to tolerate low pH, gastric juice, bile salts, and pancreatin enzymes; however notable variations in resistance were also observed and several strains demonstrated a significant ability of the strains to adhere to intestinal epithelial cells. All the isolates lacked DNase and hemolytic activity, confirming the safety of the isolates. Antibiotic susceptibility profiles indicated no harmful resistance patterns and displayed significant antagonistic activity against test pathogens. Furthermore, the study reported the absence of technological properties, specifically in terms of proteolytic, lipolytic, and amylolytic activity.DiscussionMost of the isolated strains showed significantly significant results with p <0.05 and <0.01, reinforcing the probiotic potential and safety of the isolates. These promising isolated strains hold potential as safe probiotics, offering significant health benefits.